THE FIELD WORK PLAN. - Taylor, J. B. (The Accounting Review, 1933)
The article focuses on the planning of field work in accounting. One of the acute problems facing accounting departments in collegiate schools of business is that of bridging the gap between the work in the classroom and the accountant's activities in business. The field work plan for those students who wish to enter public accounting has been developed to establish a means whereby the students may gain some valuable experience before graduation. The plan which is described in these pages is the one which has been in successful operation at the Ohio State University for about six years. Being located adjacent to several cities of considerable size, it has been possible for the university to secure the cooperation of a sufficient number of public accounting firms to make the venture a success. Participation in the field work plan on the part of the students is not compulsory. The success of the venture would be jeopardized if it were to be made so. Only the better students are privileged to take part in the field work and even in these cases, it is purely optional.